CDX2 and Ki-67 Expression in Gastric Carcinoma and Its Association with Clinocopathological Parameters - Pranjali, Chatpalli; Sulatha, Kamath; Vijaya V, Mysorekar (Asian Pacific Journal of Cancer Biology, 2022)
Background: CDX2 has been established as a good prognostic marker for colorectal carcinomas. Differentiated adenocarcinomas are characterized by higher CDX2 expression than undifferentiated tumors with stronger reactivity in intestinal phenotypes. There is a close correlation between the degree of tumor differentiation and the Ki-67 score. It was also observed that strong CDX2 expression was associated with low Ki-67 index whereas negative or dim CDX2 expression was associated with high Ki-67 index. Methods: Gastric biopsies and gastrectomy specimens with gastric carcinoma were evaluated clinicopathologically and processed for immunohistochemistry (IHC) staining to assess CDX2 and Ki-67 expression. The relationship between 2 markers and each clinicopathological parameter was evaluated. Data was statistically analysed. P<0.05 were taken for statistical significance. Results: The study was done on 57 gastric adenocarcinoma cases with mean age 56.12 years. No significant correlation was found between CDX2 & Ki-67 with clinical, gross & microscopic parameters except for tumor location and depth of invasion. Significant correlation was detected between CDX2 (p=0.04) & Ki-67 (p=0.03) with tumor location. Depth of tumor invasion was significantly associated with Ki-67 (p=0.013). No significant association between CDX2 and Ki-67 was observed. Conclusion: The statistical correlation between CDX2 & Ki-67 with clinicopathological parameters proves that CDX2 & Ki-67 to be the independent markers with respect to tumor site and depth of invasion (in case of Ki-67). But due to lack of association of CDX2 with Ki-67 further studies need to be done with higher sample size.